2007
DOI: 10.1136/jme.2005.014266
|View full text |Cite
|
Sign up to set email alerts
|

Ethical difficulties in clinical practice: experiences of European doctors

Abstract: Cultural differences may indeed influence how doctors perceive ethical difficulties. The type of help needed, however, did not vary markedly. The general structure of ethics support services would not have to be radically altered to suit cultural variations among the surveyed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
2
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 30 publications
10
137
2
16
Order By: Relevance
“…For example, a hospital ward with a hierarchic structure and unsupportive climate might have a different impact on this matter than a supportive work environment with a network of consistent boundaries regarding the psychosocial work climate. This is in line with previous research where physicians are shown to have different attitudes to and practice of confidentiality [19,20], their professional role [21,22] and coping strategies used to deal with ethical [23,24] and emotional [25] discomfort in their work. Based on the current results, these factors are likely to be associated with how physician manages emotionally-charged work situations and confidentiality.…”
Section: The Overlap Between Personal and Professional Relationshipssupporting
confidence: 76%
“…For example, a hospital ward with a hierarchic structure and unsupportive climate might have a different impact on this matter than a supportive work environment with a network of consistent boundaries regarding the psychosocial work climate. This is in line with previous research where physicians are shown to have different attitudes to and practice of confidentiality [19,20], their professional role [21,22] and coping strategies used to deal with ethical [23,24] and emotional [25] discomfort in their work. Based on the current results, these factors are likely to be associated with how physician manages emotionally-charged work situations and confidentiality.…”
Section: The Overlap Between Personal and Professional Relationshipssupporting
confidence: 76%
“…Legene er sentrale i behandlingsteamet, viktige premissleverandører, sentrale for pasient og pårørende og, ikke minst, den som ofte står ansvarlig for etisk vanskelige beslutninger. Vi vet at også leger i kommunehelsetjenesten opplever moralsk stress (43) og at de ofte mangler strategier og systemer for å hånd-tere slike utfordringer (44). Det er nødvendig å inkludere leger i den nasjonale satsingen på etikk i kommunehelsetjenesten.…”
Section: Pilotstudienunclassified
“…Treatment decisions regarding patients with advanced cancer pose complex medical and ethical challenges [1][2][3][4][5][6]. Evidence indicates that there is an increasing aggressiveness concerning the application of cancer-specific treatment near the end of life [7].…”
Section: Introductionmentioning
confidence: 99%